Emergência de nomeação de letras a partir do emparelhamento auditivo-visual em crianças com Síndrome de Down e Autismo via ensino remoto - Chizzolini, Gabriela Cabral (Universidade Federal de São Carlos, 2021)
Reading and writing are understood as important behaviors for human development, thus studies have sought ways to help students with difficulties in these learning processes. Considering the relevance and generalization of data from systematic replication to other environments and context, the importance of evaluating teaching procedures in the remote context, imposed by the current moment of the Covid-19 pandemic, for children targeted by special education, is observed. Therefore, the present study aimed to replicate the study by Hayashi et al. (2013) and to assess the emergence of letter naming from the teaching of auditory-visual pairing with children with Down syndrome and autism, in the context of remote learning, in view of the Covid-19 pandemic. Four students, of both genders, aged six to eleven years, three of them with a diagnosis of Down syndrome and one participant with a diagnosis of Autistic Spectrum Disorder, participated in the research. The activities were carried out through video conferences on Zoom platform, in which the researcher shared the tasks with the participants on their computers. A design of multiple probes between sets of letters was used. The alphabet letters were separated into eight sets of three letters and one set of two letters. Data collection was conducted individually with each participant, consisting of familiarization (pre-naming and matching to sample training) and application of teaching and probe procedure. The naming evaluation was conducted before starting each new set of letters. The capital letter was presented in the center of the computer screen and, simultaneously, on the first three trials the software presented the instruction “What letter is that?”. In the teaching condition, each trial presented the spoken letter (letter name) simultaneously with the printed letters of the set in the center of the computer screen, next to each other. The established criterion was a 100% correct responses in a block of trials. The results showed that the four participants showed an increase in correct letter naming after the teaching sessions for most of the letter sets. The four mothers rated the teaching program, the researcher's skills and also the items related to time as satisfactory and/or totally satisfactory (duration of appointments, frequency of appointments and duration of the entire procedure). In the evaluation of the participants, the four participants indicated 100% “cool” for the questions about what they thought of the researcher and about carrying out computer activities with the researcher. The data suggest that teaching letter identification may foster letter naming. Future studies should improve the procedure for conducting in a remote context.
Emergence of letter naming from auditory-visual pairing in children with Down Syndrome and Autism via remote teaching
Keywords: Ensino remoto; Nomeação de letras; Emparelhamento auditivo-visual; Síndrome de Down; Transtorno do espectro Autista; Remote teaching; Letter naming; Auditory-visual pairing; Down syndrome; Autism Spectrum Disorder; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO